2022
DOI: 10.3390/ijerph19106228
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Shoulder Dysfunction in Diabetic Patients: A Review of Literature

Abstract: Objective: Understanding the underlying mechanisms behind shoulder dysfunctions in patients with diabetes mellitus. Study Design: Systematic qualitative literature review. Participants: Patients with shoulder dysfunctions and diagnosed with impaired glucose tolerance or diabetes mellitus. Intervention: Published scientific literature containing evidence about the mechanisms of shoulder dysfunctions in the diabetic population. Articles were selected based on criteria containing diabetic population, shoulder dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…It is likely related to factors such as the deposition of advanced glycation end products (AGEs) in the shoulder joint, leading to alterations in the microstructure of collagen bers, increased production of diabetes-related in ammatory factors and proin ammatory mediators, microcirculatory disturbances associated with diabetes, and lipid metabolism disorders(Date and Rahman, n.d.). These factors can induce in ammatory responses and brotic changes in the joint capsule surrounding the shoulder joint, resulting in shoulder dysfunction (Struyf et al, 2022). Under hyperglycemic conditions, excessive sugar and protein combine to form AGEs, which accumulate within the body.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely related to factors such as the deposition of advanced glycation end products (AGEs) in the shoulder joint, leading to alterations in the microstructure of collagen bers, increased production of diabetes-related in ammatory factors and proin ammatory mediators, microcirculatory disturbances associated with diabetes, and lipid metabolism disorders(Date and Rahman, n.d.). These factors can induce in ammatory responses and brotic changes in the joint capsule surrounding the shoulder joint, resulting in shoulder dysfunction (Struyf et al, 2022). Under hyperglycemic conditions, excessive sugar and protein combine to form AGEs, which accumulate within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been confirmed that the incidence of complications and frozen shoulder ranges from 10 to 35%, and these patients have more severe stiffness, which should be actively managed [ 30 , 31 ]. There was evidence that poor long-term blood sugar control in diabetes patients was associated with an increased incidence of periarthritis, whereas there was no association between the hemoglobin A1c levels of diabetes patients and the incidence of periarthritis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has been shown to modulate the fibroblastic and inflammatory processes of hepatic cholestasis, hepatic fibrosis, and chronic allergic airway disease [ 26 , 27 , 28 ]. Type II diabetic patients have been shown to have a lower serum leptin level and are prone to suffer from SS [ 14 , 15 , 29 ]. The recognized role of leptin in mediating the fibroblastic and inflammatory processes as well as the known diabetes-leptin/diabetes-SS linkages inspired us to investigate the role of leptin in the pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%